FlingArt - Farah Touqan; Arzaq Doudar (My University, 2024)
Picture feeling a bit annoyed when you're trying to make art that's spontaneous and fun, but the usual ways make it hard to control and predict what will happen. That's what FlingArt wants to fix. Usually, when people try to make random art, it doesn't always turn out the way they want. FlingArt is like a helpful friend stepping in to solve this problem. It brings in a robot arm that you can control with a phone app. The idea is to keep the excitement of random drawing but also make the robot arm precise, like a creative assistant. The challenge is to make sure the robot arm works well, lets you control the colors just right, and is easy for everyone to use. FlingArt wants to be more than just a tool – it wants to be a fun friend that gives you surprises while also letting you create art with control.